2016
DOI: 10.1902/jop.2016.150475
|View full text |Cite
|
Sign up to set email alerts
|

Increased Periodontal Attachment Loss in Patients With Systemic Sclerosis

Abstract: Background: Patients with inflammatory rheumatic diseases and periodontitis share common pathogenetic characteristics, such as proinflammatory traits causative for tissue degradation and loss of function. The aim of the present case control study is to investigate the association between systemic sclerosis (SSc) and periodontitis.Methods: The association between SSc and periodontitis was examined in 58 SSc patients and 52 control patients, matched for age and sex. The periodontal examination included periodont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
58
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(69 citation statements)
references
References 49 publications
9
58
1
1
Order By: Relevance
“…Bilateral condylysis can be found in 7–13.7% of the cases (Haers and Sailer, ; Rout et al , ; Vincent et al , ; Doucet and Morrison, ). Temporomandibular joint (TMJ) disorders are also frequently associated with the disease (Vincent et al , ; Matarese et al , ; Pischon et al , ) and can be the consequence of mandibular resorption. The prevalence of clinical signs of TMJ dysfunction (pain, TMJ sounds, impairment of mandibular movements…) and characteristic magnetic resonance imaging (MRI) findings (disk, articular surface and bone changes) is higher in SSc patients compared to healthy controls (Matarese et al , ; Pischon et al , ).…”
Section: Orofacial Manifestationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bilateral condylysis can be found in 7–13.7% of the cases (Haers and Sailer, ; Rout et al , ; Vincent et al , ; Doucet and Morrison, ). Temporomandibular joint (TMJ) disorders are also frequently associated with the disease (Vincent et al , ; Matarese et al , ; Pischon et al , ) and can be the consequence of mandibular resorption. The prevalence of clinical signs of TMJ dysfunction (pain, TMJ sounds, impairment of mandibular movements…) and characteristic magnetic resonance imaging (MRI) findings (disk, articular surface and bone changes) is higher in SSc patients compared to healthy controls (Matarese et al , ; Pischon et al , ).…”
Section: Orofacial Manifestationsmentioning
confidence: 99%
“…Regarding tooth loss, no study highlighted a statistical difference between SSc patients and healthy controls (Chu et al , ; Baron et al , ; Pischon et al , ). However, a trend toward an increased number of missing teeth has been observed in recent studies (Baron et al , ; Pischon et al , ). Interestingly, Baron et al found a relationship between reduced manual dexterity (sclerodactyly) and the number of missing teeth (Baron et al , ,b).…”
Section: Orofacial Manifestationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In conclusion, we believe that the study by Pischon et al 1 contributed valuable information on the association between periodontal disease and SSc subtypes. However, a further analysis regarding also the association of periodontal disease and other disease characteristics of SSc, such as MRSS or mean duration of disease, should provide further and interesting information to better understand the role and the main cause of the association between periodontal disease and SSc.…”
mentioning
confidence: 74%
“…We read with great interest the recently published article by Pischon et al, 1 and, being ourselves currently involved in research on the mechanism of periodontal and temporomandibular (TMJ) diseases during systemic sclerosis (SSc), we wish to make the following observations and additions to the results obtained by these authors.…”
mentioning
confidence: 99%